The Social Integration from Regional Planning Vision - Deeb, Raida; Saleh, Haifa (Latakia University Journal -Engineering Sciences Series, 2020)
The Social Integration appears in many of the world planning political, and in several ways like a trying way to rebuild the society; according on study and analyze the skills of the human resources in any country and then to drive that skills to a specified target. The Social Integration itself is a renewed conception, every country has adopted its definition and apply it in line with the future planning scenario of its current social situation. This Research discusses the concept of social integration from a planning vision by introducing its definition, conception and components. To achieve the objective of reaching a developmentally shape of Social connections to increase the social balance and cohesion and given the largest opportunity to complete the development procese, and then to drive the human resources with the benefits of the society. The Research use the Descriptive approach analysis. And it composed of entrance of the conceptual definition of integration and social networks from a planning view, then the research explain the social integration from a philosophic view. At the end of the research we find some important results about the world social integration and the spontaneous social integration in Syria. يَظهر التكامل الإجتماعي في العديد من السياسات التخطيطية العالمية و في أوجه عديدة كمحاولة للبدء ببنى إجتماعية صحيحة؛ قائمة على دراسة و تحليل الخبرات و المهارات لدى الموارد البشربة في بلدٍ ما و توجيه هذه الخبرات والمهارات نحو هدفٍ محدد. ويعتبر التكامل الإجتماعي بحد ذاته مفهوم متجدد،فكل دولة اعتمدت تعريفه و تطبيقه بما يتناسب مع سيناريو التخطيط المستقبلي لوضعها الإجتماعي. يعمد البحث إلى مناقشة مفهوم التكامل الإجتماعي من وجهة نظر تخطيطية من خلال طرح مفهومه وتعريفه ومكوناته. بهدف الوصول لشكل تنموي للعلاقات الإجتماعية لتعزز الإستقرار والتماسك الإجتماعي وإعطاء الفرص الأكبر لسير عملية التنمية ككل،و من ثم توجيه الموارد البشرية بما يعود بالفائدة على المجتمع. يستخدم البحث المنهج الوصفي التحليلي.ويتألف البحث من مدخل تعريفي لمفهوم التكامل و طرح تعريف الشبكات الإجتماعية من وجهة نظر تخطيطية و يأتي بعدها تعريف التكامل الإجتماعي بإسلوب فلسفي تخطيطي،وينتهي البحث بمجموعة من النتائج الهامة في موضوع التكامل الإجتماعي العالمي و التكامل الإجتماعي العفوي في سوريا.